Gender social identities in English textbooks through the perspective of English as a Língua Franca - Martins de Araujo, Jessica; de Jesus Ferreira, Aparecida (BELT - Brazilian English Language Teaching Journal, 2018)
Due to the importance of textbooks in teaching, this study analyzes English as a Língua Franca (Jenkins, 2006; Kalva and Ferreira, 2011; Gimenez, 2016) in relation to issues of gender identity (Auad, 2003; Louro, 2008) and racial identity (hooks, 1995; Gomes, 2005). The article analyses how white women and black women are represented in a selected collection of textbooks and how white women and black women are framed in the global context of English as a Língua Franca. The methodology used is qualitative research (Godoy, 1995) based on documental analysis of textbooks (André, Ludke, 1986), using critical discourse analysis (Fairclough, 2001). We conclude that, in most cases, the images of women represented in these textbooks is that of white women who occupy more privileged social positions and who are native English speakers.